A National Health Service : Report of the Council of the B.M.A. to the Representative Body (1944)
1944 1944 1940s 11 pages 11 up for an area, it will obviously be desirable to make these as widely available as possible to all doctors locally engaged in the public service. Question 38.— Does the principle of free choice and the preservation of the doctor-patient relationship include free choice of patient by doctors working in Health Centres, subject to the limitation of lists? If so, what machinery is proposed to enable a doctor to obtain the transfer of a patient from his list when he feels that the association is no longer beneficial? Answer.— Yes. It is not proposed that doctors in Health Centres should be placed in any worse position in this respect than doctors in public practice outside Health Centres. Details of machinery remain to be discussed. Question 39.— Will the Minister give an assurance that patients will be allowed a reasonable choice of Health Centre if and when established, and that this choice shall no be unnecessarily limited in the case of patients living near the boundary between local authority areas? Answer.— Yes. Every endeavour will be made to secure this. Question 40.— Why is remuneration by salary considered necessary for practitioners working in Health Centres? In other words, why is competition considered to be incompatible with Health Centre practice? Question 41.— What is meant by salary or "similar" method of remuneration (p. 32)? Answer.— This subject is dealt with on pages 31-2 of the White Paper. The phrase "similar method" is meant to cover any reasonable and practicable method of remuneration which is in accord with the conception of partnership between doctors working together in a Health Centre. A possible example is a small basic salary for all, plus a pooling of the allocatable income of the centre and a sharing among its doctors on an agreed partnership basis. There are other possibilities, no doubt. Suggestions from the profession on this will be welcomed. Maternity Services Question 42.— Will every woman be entitled to the attendance of a doctor of her choice under the service throughout the ante-natal, natal and post-natal stages of maternity? Answer.— This is one of the questions which the Minister particularly wishes to discuss in more detail with the profession before any proposals can be formulated. The main problems will be to determine the extent to which a woman should have a right to require her family doctor under the new service (or any other doctor) to be present at her actual confinement, how far it should rest only with the midwife to call in the doctor if needed, and in that event whether it should normally be the woman's family doctor who is called in. Medical Officers of Health Question 43.— How is it proposed to compensate a medical officer of health for the loss of intellectual satisfaction to be derived from the varied work for which he is at present responsible when he becomes a subordinate officer in a larger authority or remains the officer of an authority shorn of the functions which have been his main interest for many years? Answer.— The underlying assumption of this question cannot be accepted. A service of the kind and the scope now proposed will clearly increase, rather than restrict, the field of interest and activity in this branch of professional life. Question 44.— Are the salaries of medical officers of health to be left to voluntary arrangement, while the rates of remuneration of general practitioners and perhaps of specialists are wholly or largely settled by central agreement for the whole country? Answer.— This is a matter which must be discussed before the new arrangements are settled. Already there is some element of central standardizing of scales for this branch of the profession, and the review of these scales will need to be considered in any case. Printed in Great Britain by Fisher, Knight and Co., Ltd., The Gainsborough Press. St. Albans. 36/H24/42